Pengaruh Promosi dan Fitur Layanan terhadap Minat Menggunakan E-Wallet Linkaja (Studi Kasus di Surabaya) - Endriyanto, Rizal; Indrarini, Rachma (Universitas Negeri Surabaya, 2022)
Increasing internet users every year, making applications also develop, one of which is an online payment application, namely Link Aja. There are several factors that have an impact on interest in using e-wallet at LinkAja, one of which is the promotion factor as well as service features. This research aims to determine the effect of promotions and service features on the interest in using the Linkaja E-Wallet (Case Study in Surabaya). This study uses a quantitative descriptive approach. The population in this study were 100 respondents from the Surabaya community who used Link Aja, using the sampling method using the random sampling method. Data collection in this research used a Likert scale. Methods Data analysis in this research uses multiple linear regression. The results of the study show that promotions and service features have a positive and significant impact on interest in using the Link Aja e-wallet. This is evidenced by the results of the R Square analysis with a value of 72.2%. This means that the variables X1 (promotion) and X2 (service features) simultaneously have an effect on the Y variable (interest in using) of 72.2% and the lack (100% - 72.2% = 72.2%) influenced by other variables outside of this study.